Development and characterisation of brown seaweed hydrolysates and fermentates with potential to reduce enteric methane - Goldy De Bhowmick; Dilip K. Rai; Oyenike Olatunji; Kieran Kilcawley; Iwona Skibinska; Emer Shannon; Deirdre Kennedy; Desmond Walsh; Leticia Mora; Maria Hayes (Scientific Reports)
Abstract Seaweeds are a valuable source of bioactive molecules widely discussed as having potential to reduce enteric methane (CH4) emissions from livestock. The brown seaweeds, Ascophyllum nodosum (Linnaeus) Le Jolis and Himanthalia elongata (Linnaeus) S. F. Gray are rich in polyphenols, specifically phlorotannins, with known antimicrobial and astringent bioactivities. Brown seaweeds can find use as animal feed additives if issues concerning their palatability and digestibility as well as the impact on protein absorption by the animal are overcome. Fermentation and hydrolysis are traditional processes used for preservation of biomass, but which may beneficially improve palatability and digestibility of feeds. The aim of this work was to assess the potential of fermented and hydrolysed brown seaweeds as agents for CH4 abatement. Ascophyllum nodosum and Himanthalia elongata of Irish origin were fermented and hydrolysed independently with commercially available lactic acid bacteria (LAB) and xylanase enzyme. Molecular weight cut off (MWCO) fractions generated from treated seaweed biomasses were assessed for their antimicrobial activities against the methanogens Methanococcus maripaludis and Methanobrevibacter ruminantium using 96-well plate and well diffusion assays. Batch experiments were carried out using anaerobic conditions at 37 °C for a period of 11 days. The A. nodosum fermentate and H. elongata hydrolysate were characterised for their polyphenol, phlorotannin, peptide, fatty acid methyl ester (FAME) and volatile compound contents using different mass spectrometry methods including GC–MS and LC–MS. Inhibition of M. maripaludis and M. ruminantium was observed in the presence of MWCO extracts generated from the treated seaweeds using the 96-well microtiter plate and well diffusion assays at concentrations of 1 mg/mL. The most antimicrobial A. nodosum MWCO fractions included the polyphenol fractions ≤ 100-kDa & 50-kDa in size, the A. nodosum phlorotannin extract ≤ 100-kDa in size and the H. elongata tannin fraction ≤ 100-kDa in size. 147 and 82 novel peptide sequences were identified in the 3 kDa MWCO fractions generated independently from the A. nodosum fermentate and H. elongata xylanase hydrolysate. Fifty volatile compounds were identified in the A. nodosum fermentate. The H. elongata hydrolysate and A. nodosum fermentate contained significant levels of palmitic acid −1536.37 µg fatty acid/g and 1139.37 µg fatty acid/g lipid, respectively.